2008
DOI: 10.1002/jso.21001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic inflammation on outcome following resection for intrahepatic cholangiocarcinoma

Abstract: Long-term outcome following resection of IHCC is poor. A pre-operative NLR >or= 5 was an adverse predictor of disease-free survival and was associated with an aggressive tumour biology profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 46 publications
(57 reference statements)
5
130
3
1
Order By: Relevance
“…Chronic inflammation and biliary irritation are, however, commonly shared among these diseases (40). These support recent findings that inflammation-based scores or parameters may be used as prognostic markers for patients with cholangiocarcinoma (36,37). In this study, we demonstrated that the inflammation-based prognostic score, GPS, is associated with the recurrence and overall survival of ICC patients and may be used as an independent prognostic marker.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Chronic inflammation and biliary irritation are, however, commonly shared among these diseases (40). These support recent findings that inflammation-based scores or parameters may be used as prognostic markers for patients with cholangiocarcinoma (36,37). In this study, we demonstrated that the inflammation-based prognostic score, GPS, is associated with the recurrence and overall survival of ICC patients and may be used as an independent prognostic marker.…”
Section: Discussionsupporting
confidence: 90%
“…Preoperative NLR is correlated with the overall survival of ICC patients, and NLR>5 is an independent risk factor for recurrence (36). GPS is an independent prognostic factor for extrahepatic cholangiocarcinoma according to a study on 62 patients (37).…”
Section: Introductionmentioning
confidence: 99%
“…The Glasgow prognostic score, reported by Forrest et al for non-small-cell lung cancer, is widely known as an indicator of SIR 23 . The gastrointestinal cancers also associated with SIR: intrahepatic cholangiocarcinoma, colorectal cancer, liver metastases of colon cancer origin, and hepatocellular cancer 19,20,[24][25][26]41 . However, only a few reports were available on perihilar cholangiocarcinoma 34,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have indicated that the state of the Systemic Inflammatory Response (SIR) provides significant information about the prognoses of a variety of cancers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Neutrophil-lymphocyte ratio (NLR), which reflects SIR, has been reported as a prognostic factor in gastrointestinal cancers, including intrahepatic cholangiocarcinoma 19 and colorectal cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation